Eurotium cristatum reduces obesity by alleviating gut microbiota dysbiosis and modulating lipid and energy metabolism. (6th July 2022) - Zhang, Bo; Ren, Daoyuan; Zhao, Aiqing; Cheng, Yukun; Liu, Yueyue; Zhao, Yan; Yang, Xingbin
Abstract: BACKGROUND: Fuzhuan brick tea (FBT) has been shown to prevent obesity, but little is known about the effect of Eurotium cristatum, a critical fungus from FBT. This study examined the effects of live E. cristatum on lipid metabolism and gut microbiota composition in high‐fat (HF) diet‐induced obese mice. RESULTS: Male HF diet‐fed mice were treated with E. cristatum for 12 weeks. The results showed that E. cristatum administration caused strong inhibition against HF‐induced body weight gain, dyslipidemia and liver oxidative stress damage. Additionally, Firmicutes and Bacteroidetes in phylum level and six types of bacterial including short‐chain fatty acids (SCFAs) producing bacteria in genus level were found to be significantly changed in E. cristatum treated mice as compared to HF fed mice. As expected, E. cristatum could increase total SCFAs levels in feces. Interestingly, E. cristatum markedly increased the proportion of Akkermansia to resist obesity. Functional prediction analysis indicated that E. cristatum changed lipid and energy metabolism. Furthermore, E. cristatum ingestion can modulate hepatic acetyl‐coa carboxylase (ACC), fatty acid synthase (FAS), sterol‐regulatory element binding protein‐1 (SREBP‐1) and adipose uncoupling protein‐1 (UCP‐1) expression. CONCLUSION: Conclusively, these findings suggest that E. cristatum can prevent the HF‐induced lipid accumulation and other complications by modulating gut microbiota, lipid and energy metabolism. © 2022 Society of Chemical Industry.